Analisis Manajemen Risiko dalam Upaya Mempertahankan Mutu Pendidikan (Studi pada SMA Dharmawangsa Medan) - Suardi, Suardi; Harahap, Ahmad Taufiq (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to find out how financial risk management actually is in the implementation of educational programs at SMA Dharmawangsa Medan, especially regarding the costs of Educational Development Contributions (SPP), which are classified as expensive/high. The main target of risk implementation is to protect Dharmawangsa schools/high schools from losses that may arise in the process of implementing educational programs in terms of determining the amount of student educational development contribution (SPP) fees. In its management, a balance is carried out between management management strategies and implementation of education with risk management so that SMA Dharmawangsa Medan will get optimal results from its operations.